Sympathectomy with T2-T3 percutaneous radiofrequency thermocoagulation method in upper extremity primary hyperhidrosis cases - Yılmaz, Ayşe; Yılmaz, Özgür (Journal of Surgery and Medicine, 2020)
Sweating is controlled by the sympathetic nervous system and helps regulate the body’s heat and electrolyte balance. Excessive sweating may be observed in about 1% of the population due to a number of reasons. Many methods are used in the treatment of hyperhidrosis, which is important for quality of life. In four patients with primary hyperhidrosis resistant to medical treatment, radiofrequency thermocoagulation of the stellate ganglion with an anterior approach and then the response of radiofrequency thermocoagulation to the T2-T3 sympathetic ganglion were evaluated. We think that it is an advantageous and successful method in terms of being less invasive and cost effective compared to other surgical methods, as the procedure time is short, patient satisfaction, hospitalization time is low. We have seen that stellate and T2-T3 sympathectomy with radiofrequency thermocoagulation method is a useful technique in the treatment of primary hyperhidrosis.